From Enynyl Esters to Functionalized Polycyclic Derivatives via Cycloisomerization and Post-Functionalization - Guelen, Simon; Blazejak, Max; Mouriès-Mansuy, Virginie; Fensterbank, Louis (Synthesis, 2016)
The post-functionalization of ketone products originating from the PtCl2-catalyzed cycloisomerization of enynyl esters is described. Post-functionalization is accomplished via diastereoselective alkylation, regioselective cyclopropane opening and regioselective Baeyer–Villiger and Beckmann rearrangements to provide functionalized polycycles.
Keywords: cycloisomerization; platinum; enynyl ester; polycyclic ketone; Baeyer–Villiger; Beckmann rearrangement; lactones; lactams